Multi-size spheroid formation using microfluidic funnels. Issue 2 (6th December 2017) - Marimuthu, M.; Rousset, N.; St-Georges-Robillard, A.; Lateef, M. A.; Ferland, M.; Mes-Masson, A.-M.; Gervais, T.
Abstract : We present a microfluidic platform for automatic multi-size spheroid formation within constant volume hanging droplets (HDs) from a single inlet loading of a constant cell concentration. Abstract : We present a microfluidic platform for automatic multi-size spheroid formation within constant volume hanging droplets (HDs) from a single inlet loading of a constant cell concentration. The platform introduces three technological improvements over the existing spheroid formation platforms: 1) cell seeding control is achieved by enrichment of a cell solution rather than dilution; 2) cell seeding in each HD is fully independent and pre-programmable at the design stage; 3) the fabricated chip operates well using a hydrophobic PDMS surface, ensuring long-term storage possibility for device usage. Pre-programmed cell seeding densities at each HD are achieved using a "microfluidic funnel" layer, which has an array of cone-shaped wells with increasing apex angles acting as a metering unit. The integrated platform is designed to form, treat, stain, and image multi-size spheroids on-chip. Spheroids can be analyzed on-chip or easily transferred to conventional well plates for further processing. Empirically, enrichment factors up to 37× have been demonstrated, resulting in viable spheroids of diameters ranging from 230–420 μm and 280–530 μm for OV90 and TOV112D cell lines, respectively. We envision that microfluidic funnels and single inlet multi-size spheroid (SIMSS) chips will find broad application in 3D biological assays where size-dependent responses are expected, including chemoresponse assays, photodynamic therapy assays, and other assays involving drug transport characterization in drug discovery.